The Use of Social Media Augmented Reality for Engaging Parents and Educating Children About Road Safety - Naser Zamani (Journal of Road Safety)
Children are vulnerable road users. While many Australian parents are social media users and augmented reality effects are a huge trend in social media, there has been little research attention on the use of social media augmented reality for educating children in road safety. In this research, seven gamified social media augmented reality learning experiences were created about six road safety subjects to engage parents and educate children aged 5-9 years in the Australian Capital Territory region, Australia. The current research aimed to investigate the results of Facebook’s augmented reality educational interventions (advertisement campaigns) and analyse the perspectives of the parents who tried the learning experiences with their children. The results of Meta’s ads manager and Spark AR Hub analytics were used to evaluate the success of Facebook augmented reality advertisements. A questionnaire was developed to gather the perspectives of parents. Ten parents completed the questionnaire and were then interviewed to discuss their responses in more depth. Augmented reality Facebook advertisements reached 200,351 people and received 719,296 impressions and 3,218 clicks. All interviewees recommended the use of augmented reality gamified learning experiences to educate children about road safety. This study provides insights into how to use social media augmented reality to engage parents and educate children.